The Effect of Latitude Differences, Sunshine Periods, Solar Radiation Quantities and Air Temperatures on Solar Electricity Generation - SARKIN, Ali Samet; DINDAR, Taner (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
Electricity  supply  has  gained  importance  with  the increase of electricity demand in the world. The energy that the sun can accept forever provides great convenience for electricity generation. In regions where the suns rays are steep, it is easier to generate  electricity  from  the  solar  energy,  whereas  in  regions where  the  suns  rays  are  horizontal,  the  electricity  production from  the  solar  energy  remains  at  a  lower  level.  In  this  study, Istanbul and Adana are compared in the northern and southern regions  of  Turkey.  These  two  cities  were  examined  for  daily sunshine  periods,  daily  and  monthly  radiation  amounts.  The effects of air temperatures and sunshine durations on the average radiation amounts have been investigated. The province of Adana has  an  annual  total  of  1568.49  kWh,  whereas  the  province  of Istanbul  has  a  total  of  1327  kWh  radiation.  When  the  annual sunshine  periods  are  examined,  it  is  97.13  hours  in  Adana  and 78.99 hours in Istanbul. It is seen that less electricity production can  be  done  year  round  in  Istanbul  province  and  the  hourly production is more than that in Adana when compared to sunrise times.  When  the  average  annual  temperatures  are  examined, Adana  province  is  19  Â°C  and  Istanbul  province  is  13.8  Â°C. Although  the  province  of  Istanbul  has  a  lower  average temperature, it has been found that it has a higher yield than the province of Adana.